The Great Recession, genetic sensitivity, and maternal harsh parenting - Lee, Dohoon (National Academy of Sciences, 2013)
Using data from the Fragile Families and Child Wellbeing Study, this study examined the effects of the Great Recession on maternal harsh parenting. We found that changes in macroeconomic conditions, rather than current conditions, affected harsh parenting, that declines in macroeconomic conditions had a stronger impact on harsh parenting than improvements in conditions, and that mothers’ responses to adverse economic conditions were moderated by the DRD2 Taq1A genotype. We found no evidence of a moderating effect for two other, less well-studied SNPs from the DRD4 and DAT1 genes.